2014
DOI: 10.1002/qj.2300
|View full text |Cite
|
Sign up to set email alerts
|

Impact of GPS radio occultation measurements in the ECMWF system using adjoint‐based diagnostics

Abstract: In this article, a comprehensive assessment of the impact of radio occultation (RO) observations in the operational ECMWF assimilation and forecast system is presented using different diagnostic tools. In particular, the observations' influence in the assimilation process and the related contribution to the short‐range forecast error of radio occultation observations is evaluated with recently developed diagnostic tools based on the adjoint version of the assimilation and forecast model. The sensitivity with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…In addition to the role radiosondes have in forecasting (e.g., Cardinali and Healy, 2014) and climatological studies (e.g., Seidel et al, 2012), recently observed anomalous evolution of the QBO (Newman et al, 2016) further bears out the need for continued radiosonde observations. Additional observations in this region will allow for more robust attribution of wave sources -whether Kelvin, Rossby, or gravity waves -to changes in zonal wind structure in the tropical stratosphere.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role radiosondes have in forecasting (e.g., Cardinali and Healy, 2014) and climatological studies (e.g., Seidel et al, 2012), recently observed anomalous evolution of the QBO (Newman et al, 2016) further bears out the need for continued radiosonde observations. Additional observations in this region will allow for more robust attribution of wave sources -whether Kelvin, Rossby, or gravity waves -to changes in zonal wind structure in the tropical stratosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies within the past decade have demonstrated the positive impact that results when RO is assimilated into numerical weather prediction models by operational forecast agencies (e.g. Cardinali and Healy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has the advantage of all-weather capability, high vertical resolution, and global coverage. RO data have significantly reduced systematic errors in global weather analysis (e.g., Healy and Thépaut, 2006;Cardinali and Healy, 2014) and are very useful for climate monitoring (e.g., Foelsche et al, 2009).…”
Section: Introductionmentioning
confidence: 99%